IS NEOBLADDER SAFE FOR HIGH GRADE BLADDER CANCER PATIENTS?: EVALUATION OF RADICAL CYSTECTOMY COMPLICATIONS AND ILEAL NEOBLADDER RECONSTRUCTION IN AMC KARIADI GENERAL HOSPITAL - Stephanie, Irene; Soedarso, Mohamad Adi (Indonesian Journal of Urology, 2019)
Objective: The purpose of this study was to evaluate complications of ileal neobladder reconstruction in high grade bladder cancer patients. Material & Methods: The descriptive study included 12 patients who underwent radical cystectomy and bladder reconstruction with ileal neobladder in Academic Medical Center Kariadi General Hospital Semarang from 2009 until 2016. Base data recorded retrospectively and followed at outpatient clinic. The complications were evaluated from perioperative care, postoperative care, and outpatients clinic. Clavien Dindo classification use to rank complication. Results: The average ages distribution range from 39-70 year. There were 2 patients with comorbid of renal failure, 11 patients with history of TUR and 1 patient underwent adjuvant external radiation. There were 11 patients in high grade bladder cancer (≥T3) and 1 patient with T2. Of the 8 patients underwent orthotopic neobladder procedure and 3 patients underwent cutaneous w-shape procedure. From the histopathology results, 10 patients with high grade transitional cell carcinoma, and 2 patients with invasive urothelial cell carcinoma. There were complication caused by neobladder-related of 1 patient with urinary leakage from ureteroileal anastomose, 1 patient with peritonitis caused by ileo-ileal anastomose leakage, and 1 patients with bowel necrosis caused by internal hernia who need re-operation. All neobladder related complication were 4/33%. From neobladder nonrelated of 1 patient with chronic renal disease and sepsis, and 1 patient with acute renal failure and hyperchlor metabolic acidosis. All of neobladder related complications described above end with mortality (2/16%), except the urinary leakage. Conclusion: Our complication and mortality radical cystectomy - neobladder related rate were 33% and 16% compare with literature show 28-64% and 5.1-8.1%, respectively. Patients selection (<T3, no comorbid) and experience according high volume operation can reduced the mortality rate.